PERBANDINGAN CAPITAL ASSET PRICING MODEL (CAPM) DAN THREE FACTORS MODEL FAMA AND FRENCH (TFMFF) DALAM MENGESTIMASI RETURN SAHAM - PITRIYANTI, KADEK MIRA; DHARMAWAN, KOMANG; GANDHIADI, G.K. (E-Jurnal Matematika; Vol 4 No 4 (2015)DO - 10.24843/MTK.2015.v04.i04.p109, 2015)
In 1996, Fama and French developed the CAPM in Three Factor Model Fama and French ( TFMFF) to analyze the relationship between risk with rate of return by adding firm size factor that is proxied by Small Minus Big (SMB) and value factor at Book to Market Ratio that is proxied by High Minus Low (HML) on the CAPM model. The aim of this research is to compare the ability of CAPM and TFMFF in estimating the returns on six types of portfolios which are formed based on firm size and BE/ME. Selected samples are stocks of LQ-45 in period of February 2014, which have passed the selection of firm profits and ROE Warren Buffett criteria. Simple linear regression and Multiple linear regression with t test and F test statistics are used to demonstrate the influence and significance level of each variable. The results showed that TFMFF was more superior than CAPM. Market risk factor consistently affected each portfolio. SMB and HML is not always significantly effect on each portfolio, such as portfolio B/H, only market risk factor has a significant effect. However, the addition of SMB factors and HML factors could increase the coefficient of determination in each formed portfolio.
Keywords: return, market risk, firm size (SMB), Book Equity to Market Equity (HML)